Keyboard warriors? Visualising technology and well-being with, for and by indigenous youth through digital stories. Issue 3 (3rd July 2019) - Loebach, Janet; Tilleczek, Kate; Chaisson, Brent; Sharp, Brian
Abstract : The Young Lives Research Laboratory is concerned with the lives of modern youth from education to technology to mental health. Technology is ubiquitous in the day to day lives of young people in Canada but little is known about the ways in which digital media affects their mental health, especially for Indigenous youth. Research seldom engages youth to clarify and or interrogate digital media and well-being. This paper addresses the dearth of empirical work and supports the development of practices which better reflect and address health impacts of digital technology on young lives. In using an empowering participatory process to provide Indigenous youth opportunity and tools to produce short digital story films helped them to reflect their unique experiences with digital media and its role in both personal and community well-being. The study also explores youth-produced filmmaking as an effective medium for communicating technology-related experiences and challenges. We share youth-produced films to exemplify the cultural process and products that arose in this project.